Secondary Bacterial Infection and Clinical Characteristics in Patients With COVID-19 Admitted to Two Intensive Care Units of an Academic Hospital in Iran During the First Wave of the Pandemic - Pourajam, Samaneh; Kalantari, Elham; Talebzadeh, Hamid; Mellali, Hamid; Sami, Ramin; Soltaninejad, Forogh; Amra, Babak; Sajadi, Mahdi; Alenaseri, Malihe; Kalantari, Forough; Solgi, Hamid (Frontiers in Cellular and Infection Microbiology, 2022)
Data on the prevalence of bacterial co-infections and secondary infection among adults with COVID-19 admitted to the intensive care unit (ICU) are rare. We aimed to determine the frequency of secondary bacterial infection, antibiotic use, and clinical characteristics in patients admitted to the ICU with severe SARS-CoV-2 pneumonia. This was a retrospective cohort study of adults with severe COVID-19 admitted to two ICUs from March 6 to September 7, 2020 in an academic medical center in Isfahan, Iran. To detect COVID-19, reverse transcription real-time polymerase chain reaction was performed and also typical pattern of CT scan was used for the diagnosis of COVID-19. Data collection included the age, gender, main symptoms, history of underlying disease, demographics, hospital stay, outcomes, and antibiotic regimen of the patient. Antimicrobial susceptibility testing was carried out according to the CLSI guidelines. During the study period, 553 patients were referred to the both ICUs for COVID-19 with severe pneumonia. Secondary bacterial infection was detected in 65 (11.9%) patients. The median age was 69.4 (range 21–95) years; 42 (63.6%) were men. Notably, 100% (n = 65) of the patients with superinfection were prescribed empirical antibiotics before first positive culture, predominantly meropenem (86.2%) with a median duration of 12 (range 2–32) days and levofloxacin (73.8%) with a median duration of nine (range 2–24) days. Most prevalent causative agents for secondary bacterial infection were Klebsiella pneumoniae (n = 44) and Acinetobacter baumannii (n = 33). Most patients with secondary bacterial infection showed extensive drug-resistance. The mortality among patients who acquired superinfections was 83% against an overall mortality of 38.1% in total admitted COVID-19 patients. We found a high prevalence of carbapenem-resistant Gram-negative bacilli in COVID-19 patients admitted to our ICUs, with a high proportion of K. pneumoniae followed by A. baumannii. These findings emphasize the importance of implementation of strict infection control measures and highlight the role of antimicrobial stewardship during a pandemic.